2017
DOI: 10.1111/tpj.13417
|View full text |Cite
|
Sign up to set email alerts
|

The mutation nrpb1‐A325V in the largest subunit of RNA polymerase II suppresses compromised growth of Arabidopsis plants deficient in a function of the general transcription factor IIF

Abstract: The evolutionarily conserved 12-subunit RNA polymerase II (Pol II) is a central catalytic component that drives RNA synthesis during the transcription cycle that consists of transcription initiation, elongation, and termination. A diverse set of general transcription factors, including a multifunctional TFIIF, govern Pol II selectivity, kinetic properties, and transcription coupling with posttranscriptional processes. Here, we show that TFIIF of Arabidopsis (Arabidopsis thaliana) resembles the metazoan complex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 82 publications
(108 reference statements)
0
2
0
Order By: Relevance
“…TFIIF function has been established from a wealth of experiments mostly performed in human and yeast, on the one hand, and using a limited number of model TATA box-containing promoters, on the other hand (Luse, 2012). The role of TFIIF, which is still incompletely understood and seem to differ in yeast and mammals, was nearly completely uninvestigated in plants until recently (Babiychuk et al, 2016). In order to describe the role of TFIIFα in Arabidopsis, we characterized different TFIIFα T-DNA insertion mutants.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…TFIIF function has been established from a wealth of experiments mostly performed in human and yeast, on the one hand, and using a limited number of model TATA box-containing promoters, on the other hand (Luse, 2012). The role of TFIIF, which is still incompletely understood and seem to differ in yeast and mammals, was nearly completely uninvestigated in plants until recently (Babiychuk et al, 2016). In order to describe the role of TFIIFα in Arabidopsis, we characterized different TFIIFα T-DNA insertion mutants.…”
Section: Resultsmentioning
confidence: 99%
“…Here, we showed by yeast two hybrid assay and BiFC in N. benthamiana leaves that the Arabidopsis Topo VI complex is associated with the general transcription factor TFIIF, via the interaction of its BIN4 subunit with the alpha subunit of TFIIF. Recent experiments on the tfIIfβ1 mutant revealed plant growth inhibition and development defects in meristematic organization responsible for stem fasciation and inflorescence impairments (Babiychuk et al, 2016). We also observed growth inhibition in tfIIfα mutants but no such developmental perturbations.…”
Section: Discussionmentioning
confidence: 99%
“…Among them, some proteins were reported to have unique functions, including the MEE5 gene, which was associated with embryo development and the development of the female gametophyte [50,51]. In addition, LSM2 [52] and RAP74 [53] regulate transcript splicing and thus influence plant development, and STZ [54] was related to drought stress resistance. These results suggested that the expression bias of the key TFs in the hybrid might be an important factor influencing the global state of transcription and the phenotype.…”
Section: Transcription Factor Analysis Of Non-additive Genesmentioning
confidence: 99%